Plants Used to Lower Blood Sugar in Elazig Central District - Cakilcioglu, U.; Turkoglu, I. (Int Soc Horticultural Science, 2009)
This study examined plants used to lower blood sugar by the folk in the central district of Elazig city. In the study, one-to-one survey was conducted with 300 diabetic individuals' who went to private hospitals for examination and pharmacies to buy drugs, from March 2005 to November 2006. The individuals' were asked which parts of the plants they used to lower blood sugar and how they prepared them, and their answers were recorded. The plants used were collected duly, converted into herbarium materials, and scientifically designated. Plants that were found to be used commonly included Urtica dioica L., Citrus limon L. Burm., Thymus haussknechtii Velen, Cucumis sativus L., Capsicum annuum L., Rumex acetosella L., Allium cepa L., Allium sativum L. and Prunus domestica L. Data from the survey forms were evaluated using SPSS 12.0 statistical software. Chi-square values were calculated, and their significance was examined. A significant correlation was found between individuals' duration of residence in the area and their status of consumption of the plants used to lower blood sugar.
1st International Medicinal and Aromatic Plants Conference on Culinary Herbs -- APR 30, 2009 -- Antalya, TURKEY
Keywords: alternative crop; folk drugs; medicinal plant; phytotherapy